Protective and therapeutic effects of natural products against diabetes mellitus via regenerating pancreatic β‐cells and restoring their dysfunction. (28th September 2020) - Semwal, Deepak Kumar; Kumar, Ankit; Aswal, Sonali; Chauhan, Ashutosh; Semwal, Ruchi Badoni
Abstract : Diabetes mellitus is a growing public health concern and an increasing interest has been raised to search for new compounds with therapeutic effects on β ‐cells. There are chronic insulin resistance and loss of β ‐cell mass in the case of type‐2 diabetes which covers about 90% of total diabetic patients. This work aims to critically review the protective and regenerative effects of various antidiabetic natural products on pancreatic β ‐cells. A thorough literature survey was conducted on the natural molecules and extracts having a protective, regenerative, and repairing effect on β ‐cells. The primary source of the literature was online scientific databases such as PubMed, Scopus, and Google Scholar. Besides, selected relevant textbooks were also consulted. Various natural molecules including berberine, curcumin, mangiferin, stevioside and capsaicin, and extracts obtained from the plants like Capsicum annum, Gymnema sylvestre, Stevia rebaudiana and Nymphaea stellate, were found to produce regenerative and anti‐apoptosis effects on β ‐cells. These natural products were also found to increase insulin secretion by stimulating β ‐cells. The present review concluded that a large number of molecules and extracts, abundantly found in nature, possess antidiabetic effect via targeting β ‐cells. Further research is warranted to use these agents as a drug against diabetes.